Diversity of subaerial coccoid cyanobacteria from Sirsi taluk, karnataka, india. (Funded work) - PRAGATI SINGH; DORIS M. SINGH (International Journal of Pharma and Bio Sciences, 2017)
Cyanobacteria, also known as Blue green algae, are the major photoautotrophic prokaryotes which are present in almost all the habitats. In this survey, species composition and occurrence of subaerial form of coccoid (non-filamentous and non-heterocytous) cyanobacteria have been studied. Around 150 algal samples were collected from various natural and artificial substrata of different habitats of Sirsi taluk (known as Heart of Western Ghats). On the basis of morpho-taxonomic observation, a total of 40 coccoid cyanobacteria have been documented which belonged to 6 families namely: Synechococcaceae (10taxa), Merismopediaceae (3taxa), Microcystaceae (13taxa), Chroococcaceae (9taxa), Xenococcaceae (3taxa) and Hyellaceae (2taxa). Cyanobacterium and Myxosarcina were least diverse represented by only one species while Gloeocapsa showed maximum diversity represented by 13 species. Tropical climate of Western Ghats provide favorable conditions for the luxuriant growth of these algal forms (and that is why, Western Ghats are known as one the major biodiversity hotspot worldwide). Despite of being the most important organisms in the ecosystem, as they are capable of photosynthesis and are the excellent source of tremendous secondary metabolites, unfortunately, no or less literature is available on coccoid cyanobacteria from tropical climate especially, in India. Most of the research has been done only in European countries which are the temperate regions. Hence, the aim of the present study is to explore the wealth of diversity of cyanobacteria in Sirsi Taluk. Taxa have been described along with camera lucida drawings.